Existence of Optimal Control for a Nonlinear-Viscous Fluid Model - Evgenii S. Baranovskii; Mikhail A. Artemov (International Journal of Differential Equations)
We consider the optimal control problem for a mathematical model describing steady flows of a nonlinear-viscous incompressible fluid in a bounded three-dimensional (or a two-dimensional) domain with impermeable solid walls. The control parameter is the surface force at a given part of the flow domain boundary. For a given bounded set of admissible controls, we construct generalized (weak) solutions that minimize a given cost functional.